Senior High School Students’ Ability in Posing System of Linear Equations in Two Variables Problems - Yemima Indah Rachmawati; Eko Sugandi; Lydia Lia Prayitno (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2019)
Problem posing is a learning approach that trains students to be able to process and communicate mathematical problems based on information obtained. This study aims to describe the ability of high school students to pose problems on the topic of system of linear equations in two variables (SLETV). This study used a quantitative descriptive study involving 60 high school students in the East Surabaya area. The results showed that students were able to submit 60 problems, consisting of 54 problems can be categorized and 6 problems could not be categorized. Based on the semantic structure of mathematics, 17 students (31.48%) were able to pose problems using 1-relationship, 13 students (24.07%) were able to pose problems using 2-relationships, 13 students (24.07%) were able to raise problems using 3-relationships, and 11 students (20.37%) were able to pose problems using 4-relationships. Based on language structure (syntax), 13 students (24.07%) were able to pose problems using assignment propositions, as many as 17 students (31.48%) were able to pose problems using relationship propositions, and 14 students (25.93%) were able pose a problem using a presupposition proposition.